Muhammadiyah Final Year Students' Perceptions of Cadre Education - Binti Anisaul Khasanah; Nurmitasari Nurmitasari; Robia Astuti (ISTAWA, 2020)
The purpose of this study was to explain the perceptions of the final year students of FKIP UMPRI towards Muhammadiyah and as a material for evaluating the advancement of Muhammadiyah cadre education methods within the university scope. This analysis is categorized as a descriptive study with a survey method. The research subjects during this study were all final year students in the 2019-2020 academic years from five study programs in FKIP UMPRI. The data analysis technique in this study was the following subsequent steps: (1) determining the score; (2) confirming the category; (3) creating the evaluation results using the program Excel Microsoft 2010. The results of this study are the perceptions of UMPRI final year students towards Muhammadiyah at the amount of antipathy to Muhammadiyah by 7%, the level of neutrality towards Muhammadiyah by 38%, the level of sympathy for Muhammadiyah by 35%, and also the level of Muhammadiyah cadres by 20%.Tujuan penelitian ini adalah untuk menjelaskan persepsi mahasiswa tingkat akhir FKIP (Fakultas Keguruan dan Ilmu Pendidikan) UMPRI (Universitas Muhammadiyah Pringsewu Lampung) terhadap Muhammadiyah dan sebagai bahan evaluasi kemajuan metode pendidikan kader Muhammadiyah di lingkungan universitas. Analisis penelitian ini metode deskriptif dengan metode survei, subjek penelitian selama penelitian ini adalah seluruh mahasiswa tingkat akhir tahun akademik 2019-2020 dari lima prodi di FKIP UMPRI. Teknik analisis data dalam penelitian ini: (1) menentukan skor; (2) mengkonfirmasikan kategori; (3) Membuat hasil evaluasi dengan menggunakan program Excel Microsoft 2010. Hasil penelitian ini adalah persepsi mahasiswa tahun akhir UMPRI terhadap Muhammadiyah yaitu tingkat antipati terhadap Muhammadiyah sebesar 7%, tingkat netralitas terhadap Muhammadiyah sebesar 38%, tingkat simpati terhadap Muhammadiyah sebesar 35%, demikian pula tingkat kader Muhammadiyah sebesar 20%.